Application of TOPSIS as a DSS in the Selection of Home Improvement Grant Recipients - Aryo Bagus Kusumadewa Tutuko; Maulana Syarief Hidayatullah; Ulla Delfana Rosiani (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2023)
This study aims to compare the TOPSIS method with the SAW and ELECTRE methods which have been presented in previous research in making decisions on home improvement grant recipients. This research utilizes data and findings from prior studies concerning the selection process for recipients of home renovation assistance, employing the SAW and ELECTRE methodologies. Using the TOPSIS method obtained results that have significant differences. The TOPSIS method provides positive and negative ideal solutions, this is more detailed in supporting the decision-making process. By displaying the web-based TOPSIS method, it is hoped that users with an interest in decision-making can access it more easily. The results indicate that the positive ideal solution may symbolize an ideal housing state, such as a well-maintained house, while the negative ideal solution may represent a subpar housing condition.